China's new role in Africa and the south a search for a new perspective - Dorothy-Grace & Firoz Manji(editor) (Oxford Fahamu, 2008)
China's global expansion is much talked about, but usually from the viewpoint of the West. This unique collection of essays written by scholars and activists from China and the global South provides diverse views on the challenges faced by Africa, Latin America, and Asia as a result of China's rise as a significant world economic power. Chinese aid, trade, and investments?driven by the needs of its own economy?present both threats and opportunities for the South, requiring a nuanced analysis that goes beyond simplistic caricatures of "good" and "evil." This book provides a fresh perspective that focuses on the economic, social, and environmental impact of China's expansion. It represents the first attempt to establish a dialogue between civil society in China and the global South. Contributors include Walden Bello, Luk Tak Chuen, Shalmali Guttal, Yu Xiaogang, Ding Pin, Xu Weizhong, Dot Keet, Barry Sautman, Yan Hairong, Lucy Corkin, Ali Askouri, Yuza Maw Htoon, Khin Zaw Win, Alexandre de Freitas Barbosa, Fu Tao, and Peter Bosshard.
Includes bibliographical references and index.
Keywords: China--Foreign relations--Africa.